2023
DOI: 10.3390/pathogens12040595
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Yeast Diversity in the Female Genital Tract: An Exploration of Spatial Distribution and Antifungal Resistance

Abstract: Candida albicans is the leading cause of vulvovaginal yeast infections; however, other species are becoming relevant in this niche. The spatial distribution of these fungi in the female genital tract remains poorly understood. In this study, swab samples were collected from 33 patients, first from the anterior vulva and then from the upper third and right lateral wall of the vagina: 16 were with symptoms of vulvovaginal candidiasis and 17 were without characteristic symptoms; furthermore, the genus and species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Furthermore, Rhodotorula spp. and C. parapsilosis were more commonly associated with host colonization, while C. albicans were more associated with infection [14]. In another study, we found that C. albicans was the most prevalent Candida spp., both in acute and chronic cases of vaginal candidosis [15].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Furthermore, Rhodotorula spp. and C. parapsilosis were more commonly associated with host colonization, while C. albicans were more associated with infection [14]. In another study, we found that C. albicans was the most prevalent Candida spp., both in acute and chronic cases of vaginal candidosis [15].…”
Section: Introductionmentioning
confidence: 64%
“…In a recent study, we identified that the most prevalent species detected in clinical vaginal samples was C. albicans, present in 63.6% (21/33) of patients, followed by Rhodotorula spp. in 51.5% (17/33), C. parapsilosis in 15.2% (5/33), Naganishia glabratus in 9.1% (3/33), C. tropicalis in 3.0% (1/33), and Saccharomyces cerevisiae in 3.0% (1/33) [14]. Furthermore, Rhodotorula spp.…”
Section: Introductionmentioning
confidence: 99%
“…1 Candida albicans is the most commonly found species, accounting for approximately 20% to 90% of the recovered isolates. 2 One of the main virulence mucosa. Subsequent invasion by hyphae activates epithelial signaling pathways leading to pro-inflammatory responses and biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of VVC infection, patients may experience itching, redness, and burning of the vulva and vaginal mucosa, leading to frequent urination, dyspareunia, dysuria, and a consequent impaired quality of life Candida albicans is the most commonly found species, accounting for approximately 20% to 90% of the recovered isolates . One of the main virulence factors of C. albicans is the yeast-to-hypha transition, which occurs after adhesion to the epithelial cells of the vulvovaginal mucosa.…”
Section: Introductionmentioning
confidence: 99%